2022
DOI: 10.1073/pnas.2205610119
|View full text |Cite
|
Sign up to set email alerts
|

Rate of atmospheric brown carbon whitening governed by environmental conditions

Abstract: Biomass burning organic aerosol (BBOA) in the atmosphere contains many compounds that absorb solar radiation, called brown carbon (BrC). While BBOA is in the atmosphere, BrC can undergo reactions with oxidants such as ozone which decrease absorbance, or whiten. The effect of temperature and relative humidity (RH) on whitening has not been well constrained, leading to uncertainties when predicting the direct radiative effect of BrC on climate. Using an aerosol flow-tube reactor, we show that the whitening of BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
72
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 72 publications
4
72
0
Order By: Relevance
“…Light-absorbing organic aerosol, or brown carbon (BrC), impacts climate directly by scattering and absorbing sunlight , and indirectly by influencing cloud formation and properties. , Together, these effects are predicted to result in a significant overall warming effect for BrC, , but there are uncertainties regarding both the direct and indirect radiative effects. Primary BrC, including nitrophenols emitted from biomass burning, may react with light or oxidants and ultimately whiten during its atmospheric lifetime. Initially nonabsorbing emissions may react to give secondary BrC, potentially counteracting the whitening of primary BrC to some extent. If primary BrC from a particular source were not highly absorbing or if it were to whiten rapidly, the warming effect of BrC would be lessened. Furthermore, if BrC were to become more hygroscopic during its atmospheric lifetime, generally consistent with oxidation, the cooling effect of enhanced cloud activation would be increased.…”
Section: Introductionmentioning
confidence: 99%
“…Light-absorbing organic aerosol, or brown carbon (BrC), impacts climate directly by scattering and absorbing sunlight , and indirectly by influencing cloud formation and properties. , Together, these effects are predicted to result in a significant overall warming effect for BrC, , but there are uncertainties regarding both the direct and indirect radiative effects. Primary BrC, including nitrophenols emitted from biomass burning, may react with light or oxidants and ultimately whiten during its atmospheric lifetime. Initially nonabsorbing emissions may react to give secondary BrC, potentially counteracting the whitening of primary BrC to some extent. If primary BrC from a particular source were not highly absorbing or if it were to whiten rapidly, the warming effect of BrC would be lessened. Furthermore, if BrC were to become more hygroscopic during its atmospheric lifetime, generally consistent with oxidation, the cooling effect of enhanced cloud activation would be increased.…”
Section: Introductionmentioning
confidence: 99%
“…The viscosity of BB-POA from the pyrolysis of pine wood has been studied previously and was found to depend strongly on relative humidity (RH) and temperature. 56 Similarly, the diffusion rates of organic molecules in BB-POA, which are inversely related to particle viscosity, were also found to depend on RH. 57 In contrast to BB-POA, much less is known about the viscosity of BB-SOA.…”
Section: Introductionmentioning
confidence: 86%
“…81-83 Schnitzler et al (2022) showed that the whitening of BB-POA depends on the viscosity of the BB-POA, with whitening rates strongly decreasing with increasing particle viscosity. 56 The strong contrast in viscosity between BB-POA and phenolic BB-SOA (Fig. 3) could have considerable implications for the whitening rates of BB-POA in the atmosphere.…”
Section: Soa Type O/cmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Compounds that strongly absorb visible radiation are constituents of brown carbon (BrC), 9,10 which contributes a warming effect on climate, the magnitude of which remains uncertain. 11,12 These compounds can be emitted into the atmosphere directly from the source (i.e., primary) or form downwind from the source (i.e., secondary), 13,14 as a result of reactions involving light or oxidants, including OH and NO 3 radicals. 15,16 Constituents of BrC can undergo functionalization or oligomerization that may give more-absorbing products, causing absorption enhancement, or fragmentation that may give less-absorbing products, causing whitening.…”
Section: ■ Introductionmentioning
confidence: 99%